Causes of Homelessness in Las Vegas: Findings from a HELP USA Survey of People Experiencing Unsheltered Homelessness - Parulkar, Ashwin (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Las Vegas presents a unique case in urban America for examining homelessness. Like other metros, the struggle for this city’s working class is shaped by high rents and deep poverty. Yet, two local factors create distinct risks to homelessness. First, the city’s unaffordable housing market is partly the outcome of the “financialization” of the large, foreclosed property supply by private investors that began during and continued after the Great Recession. Second, the economic precarity of workers is partly driven by their often highly mobile (out-of-state and immigrant) status in an expanding high-end service industry that offers little job security and low wages. This study investigates the major causes of and pathways into homelessness among unsheltered people in Las Vegas by integrating structural and individual risk factors within a Latent Class Analysis (LCA) framework. Using a survey of 360 respondents, this study identifies distinct subgroups by applying LCA to data on housing and employment insecurity, health and substance use challenges, adverse childhood experiences (ACEs), such as loss and abuse, and histories of institutionalization (including foster care, carceral, and mental health systems). Grounded in social ecological and structural theories of homelessness, the analysis evaluates the extent to which homelessness in Las Vegas is driven by structural risk factors, individual risk factors, and/or their interactions. Three classes emerged. Class 1 (66%) became homeless due to unemployment and exhibited fewer additional vulnerabilities, indicating that structural factors contributed to homelessness for most of the surveyed population. Homelessness among other respondents, represented by class 2 (11%) and class 3 (23%), arose from a synthesis of particular individual and structural risk factors, revealing discrete pathways that nuance the social ecological perspective. Women and people with physical disabilities who experienced cumulative childhood traumas marked, for example, by loss, foster care involvement, and poverty were driven into homelessness upon eventual experiences of violence, conflict or loss (class 2). People with potentially high degrees of clinical severity marked by serious mental health burdens and substance use problems with histories of institutionalization and who experienced childhood traumas of loss were driven into homelessness by these health problems and the loss of housing such as an eviction (class 3). Policy recommendations include employment programs, expanded transitional and permanent supportive housing with social services for those with complex needs, and tenant protections to reduce rent burdens.